2018
DOI: 10.1002/pc.24785
|View full text |Cite
|
Sign up to set email alerts
|

The combined effects of wet–dry cycles and sustained load on the bond behavior of FRP–concrete interface

Abstract: Effective bonding between the adherents plays a key point when dealing with the retrofit of concrete structures by using fiber-reinforced polymers (FRPs). However, lack of adequate studies on the long-term performance of the bond behavior of FRP-concrete interface under harsh environments will inhibit their application in the repair of aged structures. Therefore in this study, 60 double-lap shear-bonded FRPconcrete composite specimens were designed and tested under wet-dry cycles and sustained loading. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…The details of the experimental programme can be found in our previously published article [ 3 ]. Here, only a brief description is provided to ensure the completeness of the paper.…”
Section: Experimental Programmementioning
confidence: 99%
See 1 more Smart Citation
“…The details of the experimental programme can be found in our previously published article [ 3 ]. Here, only a brief description is provided to ensure the completeness of the paper.…”
Section: Experimental Programmementioning
confidence: 99%
“…Externally bonded fibre-reinforced polymer (FRP) composites have been shown to be an effective strengthening method for existing engineering structures due to its excellent tensile strength, light weight, corrosion resistance, and easy tailoring [ 1 , 2 ]. The performance of this method depends on adequate bond strength between the FRP and the concrete, which ensures the stress transmission between and coordination of FRP and concrete [ 3 ]. Therefore, numerous studies have been conducted on the bond mechanism of the FRP-to-concrete interface, including experimental studies [ 4 , 5 , 6 , 7 ], theoretical analysis [ 8 , 9 , 10 , 11 ], and finite-element simulations [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many scholars have carried out experimental studies on the durability of FRP (He et al, 2020; Al-Safy et al, 2014; Dong et al, 2018). The relationships between the ultimate strength, elastic modulus, elongation, and degradation time of FRPs under different environmental conditions have been studied (Liang et al, 2019; Yang et al, 2018; Yu, 2018). The durability of FRP has been measured by applying the reduction of ultimate strength, and the degradation model and degradation law of FRP sheets in different environments have been established (Hedayat and Baniasadizade, 2015; Xu, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A model for calculating the degradation of CFRPconcrete bond interface was proposed, and an environmental coefficient was introduced to predict the service life of CFRP-concrete structures. Liang et al (2019) investigated the bond behavior of CFRP-concrete specimens under wetdry environment (5% NaCl water for 0 to 360 days). It was found that the failure mode turns to the interface failure of adhesive and concrete as the wet-dry cycle increases.…”
Section: Introductionmentioning
confidence: 99%